Endostatin binds nerve growth factor and thereby inhibits neurite outgrowth and neuronal migration in-vitro - Ahmad, Abraham Al (Brain Res, 2010)
Endostatin (ES), the C-terminal fragment of collagen XVIII known for its anti-angiogenic properties, is associated with neurological diseases in mammals. In this study, we investigated the effect of ES on nerve growth factor (NGF)-induced neuronal differentiation, migration, neuritogenesis, and neurite extension. ES partially inhibited PC12 cell differentiation and cerebellar granule cell migration. In addition, neurite outgrowth was inhibited in a concentration-dependent manner. This effect was also matrix-dependent, as we observed better inhibition on PC12 cells grown on collagen compared to laminin matrices. Furthermore, we observed partial NGF depletion by collagen and ES, but not by laminin suggesting that NGF–matrix interactions may be important for promoting neuritogenesis, competitive inhibition by ES or low affinity matrix impairs PC12 differentiation and neurite outgrowth. Finally, using a biosensor technique, we demonstrated a direct interaction between NGF and ES suggesting the mechanism of action of ES may involve NGF sequestration. In conclusion, our study demonstrates the inhibitory effect of ES on different steps of neurogenesis including cell differentiation and migration and neuritogenesis by NGF sequestration. Such sequestration may compromise brain repair following injury, but also may play important role in axon finding as well as a potent therapeutical target in diseases involving abnormal elevated neurotrophic growth factor levels. Taken together, this study raises the consideration of ES as a double-edge sword that carries both deleterious and putative therapeutical effects.